Peran Pikiran Bawah Sadar (Subconscious Mind) dalam Proses Menulis dan Pembelajaran Naratif - Zainurrahman Zainurrahman (Kantor Bahasa Provinsi Maluku Utara, 2016)
Human subconscious mind is rich of motivation, creativity, and emotion. If everyone is able to access it, then everyone can utilize their subconscious treasures for various needs and purposes, including education and learning purposes. One of the learning models which includes accessing subconscious mind is hypnoteaching. Hypnoteaching includes 5 complex elements; they are quantum teachinglearning, power teaching, neuro-linguistic programming, accelerated learning, and hypnosis. This shows that without one of these five elements, then the application of hypnoteaching learning model is not effective. Among these five elements, hypnosis is the one part which touches the subconscious mind. in narrative writing (and learning) process, subconscious mind plays a very important role. One of the roles is digging the information or data stored in it, then displaying it visually (mental image) and giving us chance to create and structure them to be a story or a narrative. This article provides information how pure hypnosis (not hypnoteaching) can be utilized in the narrative learning or writing process